Is it possible with two words to touch three subjects? - Kašuba, Romualdas; Rudalevičienė, Regina (Lietuvos matematikos rinkinys, 2015)
In the paper an attempt to describe what a unexpected consequencies a comparison of some two (even strickingly similiar) matters might imply.
Keywords: The specifics of problem posing and comparison of consequences; distinction of solutions of similar problems; the posing of problems and their real accessibility; concrete number as possible breaking element in representing of tasks; the strategy of problem posing and its heuristical context